Shifting employment : undeclared labour in construction - Cremers, Jan; Janssen, Jörn (Brussels, 2006)
"The main aim of this research was to analyse the phenomenon of undeclared labour in the construction industry and to assess best practices to prevent and combat undeclared labour. The share of undeclared labour in construction output and employment appears to be much higher in all countries than the average share of undeclared labour in GDP or overall employment. The authors found enough evidence to conclude that: the highest occurrence of undeclared labour relates to work carried out by workers next to their regular job. the status of self-employment is abused, with bogus practices by national citizens as well as foreign ‘independent’ workers entering the market through labour-only subcontracting. dubious agencies and labour traffickers supplying cheap illegal labour mainly from abroad have returned. But “illegal never complain and work hard” and only little “persuasion” is needed because of their illegal status. "